Factors Influencing the Increase in Mudarabah Savings: Evidence from Sharia Banks in Indonesia - Bambang Iswanto; Risma Nurriani; Idhafiyyah Anwar; Ahmad Tibrizi Soni Wicaksono; Muhammad Nur Faaiz Fathah Achsani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This research aims at discovering the effect of public bank's interest rate, Rupiah exchange rate, deposit profit sharing of public sharia banks and number of branch offices on the amount of mudarabah savings deposit in public sharia banks in Indonesia. It used Multiple Linear Regression Analysis to test 60 data samples from 12 banks located in Indonesia based on the public sharia banks’ monthly reports from 2017 to 2021. The research result showed that public bank's interest rate had no partial effect on the amount of mudarabah savings deposit and Rupiah exchange rate, deposit profit sharing and number of branch offices partially affected the amount of mudarabah savings deposit. Simultaneously, however, public bank's interest rate, Rupiah exchange rate, deposit profit sharing and number of branch offices had an influence on the amount of mudarabah savings deposit. As a primary funding source, mudarabah deposit plays an important role in a bank’s stability since it is the main element to reduce the bank liquidity risk. The implication of this study is that it is important for banks to have a policy that (1) maintain a certain amount of deposit savings by considering the macroeconomic condition, namely the exchange rate of currency used in the global economic trade and (2) maintain the performance of bank’s internal factors such as profit-sharing and number of branch offices as an attempt to expand the networkto increase the mudarabah deposit market share.